Wake on Wireless: An Event Driven Energy Saving Strategy for Battery Operated Devices - Bahl, Victor; Sinclair, Mike; Shih, Eugene (he Eighth ACM International Conference on Mobile Computing and Networking, 2002)
The demand for an all-in-one phone with integrated personal information management and data access capabilities is beginning to accelerate. While personal digital assistants (PDAs) with built-in cellular, Wi-Fi, and Voice Over-IP technologies have the ability to serve these needs in a single package, the rate at which energy is consumed by PDA-based phones is very high. Thus, these devices can quickly drain their own batteries and become useless to their owner. In this paper, we introduce a technique to increase the battery lifetime of a PDA-based phone by reducing its idle power, the power a device consumes in a “standby” state. To reduce the idle power, we essentially shut down the device and its wireless network card when the device is not being used—the device is powered only when an incoming call is received. Using this technique, we can increase the battery lifetime by up to 115%. In this paper, we describe the design of our “wake-on-wireless” energy-saving strategy and the prototype device we implemented. To evaluate our technique, we compare it with alternative approaches. Our results show that our technique can provide a significant lifetime improvement over other technologies.